Non-isothermal physical and chemical processes in superfluid helium - Gordon, E.B.; Kulish, M.I.; Karabulin, A.V.; Matyushenko, V.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Metal atoms and small clusters introduced into superfluid helium (He II) concentrate there in quantized vortices to form (by further coagulation) the thin nanowires. The nanowires’ thickness and structure are well predicted by a double-staged mechanism. On the first stage the coagulation of cold particles in the vortex cores leads to melting of their fusion product, which acquires a spherical shape due to surface tension. Then (second stage) provided these particles reach a certain size they do not possess sufficient energy to melt and eventually coalesce into the nano-wires. Nevertheless the assumption of melting for such refractory metal as tungsten, especially in He II, which possesses an extremely high thermal conductivity, induces natural skepticism. That is why we decided to register directly the visible thermal emission accompanying metals coagulation in He II. The brightness temperatures of this radiation for the tungsten, molybdenum, and platinum coagulation were found to be noticeably higher than even the metals’ melting temperatures. The region of He II that contained suspended metal particles expanded with the velocity of 50 m/s, being close to the Landau velocity, but coagulation took place even more quickly, so that the whole process of nanowire growth is completed at distances about 1.5 mm from the place of metal injection into He II. High rate of coagulation of guest metal particles as well as huge local overheating are associated with them concentrating in quantized vortex cores. The same process should take place not only for metals but for any atoms, molecules and small clusters embedded into He II.